Commonwealth of Massachusetts. By His Excellency James Bowdoin, Esquire, Governour of the Commonwealth of Massachusetts. An address, to the good people of the Commonwealth. : a spirit of discontent, originating in supposed grievances, having ... stimulated many of the citizens in several of the counties of this Commonwealth, to the commission of acts subversive of the government ... Given at the council-chamber, in Boston, the 12th day of January, 1787 . ([Adams and Nourse], 1787)
January 12, 1787 Address of Governor James Bowdoin to the people of Massachusetts regarding various actions taken by the legislature and the governor to restore peace and harmony in response to rebellious acts from some of the citizens, most likely, as part of Shay's Rebellion, and defending the use of force to end the rebellion.